(untitled) (In situ, 2025)
Systematic research of the shipwreck near the islet of Gnalić, which began in 2013, continued in August 2024. The objectives of this campaign were to remove all elements of the master frame, continue excavation toward the bow, and retrieve barrels from the stern and central parts of the ship. All goals were successfully achieved; however, the discovery of a significant number of new barrels in the bow section considerably slowed the pace of the underwater excavation. One fully preserved barrel was found in the central stern section. After the master frame was removed, it was divided into nine segments, documented using photogrammetry, and left protected on the seabed until the next research campaign.